The Role of Information Systems in Early Detection of Pregnant Psychological Issue: A Systematic Review - Runjati; Suryono; Budiyati, Arum (Alta Dharma Publisher, 2022)
Introduction: During pregnancy, there can be very critical psychological changes. Early detection with verbal and paper-based questionnaires has not been able to help. A fast and practical information system is used in health services to support the success of early detection of anxiety in pregnant women. Objective: This study aims to analyze the role of information systems in the early detection of the psychological health of pregnant women and recommendations for improving midwifery services. Methods: This study is a systematic review that uses the PRISMA protocol guidelines. The databases searched in this study were articles from PubMed, Google Scholar, and Science Direct. Results: There are four relevant articles reviewed in this study. Studies show that information systems effectively detect the psychological health of mothers during pregnancy. Conclusion: Overall, the research indicates that the information system is a platform that has a perceived impact on the psychological well-being of pregnant women. Recommendation: Further study need to be consider the information system to detect the issue of psychological among pregnant women